Clinical recommendations for high altitude exposure of individuals with pre-existing cardiovascular conditions: a joint statement by the European Society of Cardiology, the Council on Hypertension of the European Society of Cardiology, the European Society of Hypertension, the International Society of Mountain Medicine, the Italian Society of Hypertension and the Italian Society of Mountain Medicine - Parati, Gianfranco; Bärtsch, Peter (European heart journal, 2018)
Abstract. Take home figureAdapted from Bärtsch and Gibbs2 Physiological response to hypoxia. Life-sustaining oxygen delivery, in spite of a reduction in the pa